2010
DOI: 10.3892/etm.2010.145
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and in vivo evidence of synergy of a herbal extract compared to its most active ingredient: Rabdosia rubescens vs. oridonin

Abstract: Abstract. Rabdosia rubescens is a herbal root extract of traditional Chinese medicine (TCM) used to treat inflammatory diseases and oral cancers. a key principle of tcm is that multiple ingredients in a plant extract are more effective and less toxic than a single purified active ingredient or a purified drug derived from a plant product. Rabdosia rubescens extract (RRE) contains terpenoids and flavonoids, but the most active ingredient within the extract attributed to the inhibition of cancer is the kaurene d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…A key principle of traditional Chinese medicine is that multiple ingredients in a plant extract are more effective and less toxic than a single purified active ingredient or a purified drug derived from a plant product (Wong et al, 2010). Based on this concept, the whole N. sativa seed was the choice in this study to be less toxic, easy to administrate and more effective than its single purified active ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…A key principle of traditional Chinese medicine is that multiple ingredients in a plant extract are more effective and less toxic than a single purified active ingredient or a purified drug derived from a plant product (Wong et al, 2010). Based on this concept, the whole N. sativa seed was the choice in this study to be less toxic, easy to administrate and more effective than its single purified active ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…Research showed that oridonin was one of the most important antitumor active ingredient of Rabdosia rubescens (33)(34)(35)(36). Our previous studies showed that oridonin could arrest the cell cycle in G 2 /M phase in human gastric cancer SGC-7901 cells (3).…”
Section: Discussionmentioning
confidence: 99%
“…H. Hara [12], [13]. In fact, the majority of recent studies that evaluate the bioactivity of oridonin have focused on I. rubescens as the source of the compound [10], [14][16].…”
Section: Introductionmentioning
confidence: 99%